The impact of outdoor education camp program in building resilience among university students - Samsudin, Shamsulariffin; Tengku Kamalden, Tengku Fadilah; Aziz, Azlizam; Ismail, Mohd Hafizal; Yaakob, Sam Shor Nahar; Farizan, Noor Hamzani (UiTM Press, 2021)
Resilience is gained through life experiences that local university students lack from a classroom environment. This study investigated the effect of outdoor education camp programs on the levels of resilience among Physical Education students from two selected universities in Malaysia. A questionnaire was utilized as the primary research tool in this study to assess the participants' perceptions and knowledge acquisition as well as their level of resilience toward the outdoor education camp programs. A total of 162 undergraduate students were studied using a pre-test and post-test approach and a modified version of the Connor-Davidson in a 25 items self-report scale. Analysis of paired t-test showed differences in factors involved in resilience variables, personal competence, instincts and tolerance of negative behavior, positive acceptance of change, control, and spiritual influence. The findings indicated a positive effect towards resilience upon completion of the 14-day outdoor education camp program. A multivariate analysis of variance (MANOVA) was carried out to evaluate if participation in the outdoor education program influenced participants' perceived level of resilience. Overall, there were statistically significant increases in resilience levels from the pre-test to the post-test stage. These results lead to the need for in-depth research into the assessment of internal factors in an outdoor camp program to provide valuable information on the effect of the intervention and implications towards enhancing resilience of the participants in low to high-risk activities.